2008
DOI: 10.1007/s00406-008-5006-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological impairments predict the clinical course in schizophrenia

Abstract: To add to the open question whether cognitive impairments predict clinical outcome in schizophrenia, a sample of 125 first episode patients was assessed at the onset and over one year of controlled long-term treatment within a study of the German Research Network on Schizophrenia. No relapse according to predefined criteria occurred within the first year, but a total of 29 patients fulfilled post-hoc criteria of "clinical deterioration". Impairments in cognitive functioning assessed by the Trail-Making Test B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 51 publications
0
18
0
3
Order By: Relevance
“…Cognitive impairment is a core feature of schizophrenia (Gold and Harvey, 1993;Green et al, 2000) and is present early in the course of the illness (Mesholam-Gately et al, 2009;Bozikas and Andreou, 2011). A number of studies have reported a 1-2 standard deviation (SD) decline in the performance on tests of multiple cognitive domains, including attention, executive function, memory, and processing speed, compared with healthy volunteers (Saykin et al, 1994;Bilder et al, 2000;Wolwer et al, 2008;Mesholam-Gately et al, 2009). These cognitive deficits have been shown to largely determine social and occupational functioning (Green, 1996;Meltzer et al, 1996), as well as quality of life (QOL) in patients with schizophrenia (Matsui et al, 2008;Tomida et al, 2010;Woon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairment is a core feature of schizophrenia (Gold and Harvey, 1993;Green et al, 2000) and is present early in the course of the illness (Mesholam-Gately et al, 2009;Bozikas and Andreou, 2011). A number of studies have reported a 1-2 standard deviation (SD) decline in the performance on tests of multiple cognitive domains, including attention, executive function, memory, and processing speed, compared with healthy volunteers (Saykin et al, 1994;Bilder et al, 2000;Wolwer et al, 2008;Mesholam-Gately et al, 2009). These cognitive deficits have been shown to largely determine social and occupational functioning (Green, 1996;Meltzer et al, 1996), as well as quality of life (QOL) in patients with schizophrenia (Matsui et al, 2008;Tomida et al, 2010;Woon et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…45 Various neurocognitive phenotypes have been proposed as endophenotypes 46 and been shown to predict disease outcome. 47 Mojtabai and colleagues 48 have shown that the neuropsychological profile of SZ patients is distinct from that of psychotic affective disorders—which further emphasizes the need for diagnostic specificity. In this section, we first consider longitudinal cognitive changes separately for short- and long-term follow-up periods, followed by an overview of schizophrenia in late adulthood.…”
Section: Cognition: Longitudinal Studiesmentioning
confidence: 99%
“…A number of studies have reported a 1–2 standard deviation decline in performance on tests of multiple cognitive domains, including attention, executive function, memory, and processing speed, compared to healthy individuals 35,3739. These cognitive deficits largely determine social and occupational functioning, as well as quality of life (QOL) in patients with schizophrenia 40…”
Section: Pharmacological Profilementioning
confidence: 99%